PERAN KOMPETENSI PROFESIONALISME GURU PAI DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK - Muh. Idham Badrussalam Rosyidin (UNISAN JURNAL, 2024)
The point of this exploration is to examine the job of educators’ expert abilities in further developing understudy finding out about Islamic Strict Training (PAI) and spreading the viability of the utilization of data innovation as a learning asset in understudy learning in PAI subjects. . The exploration technique utilized is library research, specifically gathering and breaking down data from different sources in regards to the topic. In view of information discoveries in the field and as made sense of in the past parts, a few ends can be drawn with respect to the definition of the issue brought up in this examination. These issues are as per the following: In view of the consequences of the writing concentrate on that has been done, it tends to be reasoned that the job of PAI educator proficient ability is vital in further developing understudy learning accomplishment in PAI subjects. PAI instructors who have satisfactory capability can give a superior growth opportunity to understudies. Aside from that, the utilization of data innovation as a learning asset can likewise further develop understudy learning results in PAI subjects. Data innovation can make it more straightforward for understudies to get to data and empower them to advance autonomously and intuitively. Hence, to further develop understudy learning accomplishment in PAI subjects, it is suggested that PAI educators foster better proficient abilities and use data as a compelling learning asset. This is supposed to work on the nature of PAI learning and increment seriousness in the computerized period